2014
DOI: 10.1007/s00453-014-9966-5
|View full text |Cite
|
Sign up to set email alerts
|

On Group Feedback Vertex Set Parameterized by the Size of the Cutset

Abstract: Copies of full items can be used for personal research or study, educational, or not-forprofit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. Publisher statement:The final publication is available at Springer via http://dx.doi.org/10.1007/s00453-014-9966-5 A note on versions:The version presented here may differ from the published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Guillemot [17] was the first to study GFVS in terms of parameterized complexity, and showed FPT algorithms parameterized by k + |Γ|. Cygan et al [11] showed GFVS to be FPT parameterized by k alone, even when the group is given only implicitly by an oracle supporting group operations. Iwata et al [22] showed a faster algorithm, solving GFVS in time O * (4 k ) using an LP-branching approach, also in the oracle model.…”
Section: Questionmentioning
confidence: 99%
“…Guillemot [17] was the first to study GFVS in terms of parameterized complexity, and showed FPT algorithms parameterized by k + |Γ|. Cygan et al [11] showed GFVS to be FPT parameterized by k alone, even when the group is given only implicitly by an oracle supporting group operations. Iwata et al [22] showed a faster algorithm, solving GFVS in time O * (4 k ) using an LP-branching approach, also in the oracle model.…”
Section: Questionmentioning
confidence: 99%
“…At the same time, many variants of FVS received significant attention, including Subset FVS [10,16,21], Group FVS [9,13,16,19], Connected FVS [23], or Simultaneous FVS [3].…”
Section: Introductionmentioning
confidence: 99%